The system of early warning on strong sub-crustal earthquakes of the Vrancea zone - V. M. Shapka; A. I. Lyashchuk; Yu. A. Andrushchenko; I. V. Korniyenko; V. V. Grabchenko (Геофизический журнал, 2016)
The article is devoted to the issue of seismological monitoring and automatic warning of the personnel of potentially hazardous manufactures on the approaching of seismic threat and warning the population, in order to advance their preparation and minimize negative consequences. International experience of creating a system of early warning of earthquakes has been analyzed. The main factors, which determine the seismicity of the territory of Ukraine, have been considered. A model of the system of early earthquake warning for the objects of critical infrastructure of Ukraine has been proposed.